Contribution of understorey vegetation to evapotranspiration partitioning in apple orchards under Mediterranean climatic conditions in South Africa - Ntshidi, Z.; Dzikiti, S.; Mazvimavi, D.; Mobe, N.T. (Agricultural water management, 2021)
Orchard evapotranspiration (ET) is a complex flux which has been the subject of many studies. It often includes transpiration from the trees, cover crops and weeds, evaporation from the soil, mulches and other orchard artefacts. In this study we investigated the contribution of the orchard floor evaporative fluxes to whole orchard ET focusing on the transpiration dynamics of understorey vegetation which is currently not well known. Data on the partitioning of ET into its constituent components were collected in apple (Malus Domestica Bork) orchards with varying fractional canopy cover. The study orchards were in the prime apple growing regions in South Africa. The orchards were planted to the Golden Delicious/Reinders and the red cultivars (i.e. Cripps’ Pink/ Royal Gala/Fuji). Tree transpiration was quantified using the heat ratio method and the thermal dissipation sap flow techniques. Understorey transpiration was measured at selected intervals using micro stem heat balance sap flow gauges calibrated against infrared gas analyser readings. Orchard ET was measured using an open path eddy covariance system while the microclimate, radiation interception, and soil evaporation were also monitored. Orchard floor evaporative fluxes accounted for as much as 80% of the measured ET in young orchards with dense understorey vegetation that covered most of the orchard floor. In these orchards the understorey transpiration was of the same order of magnitude as the bare moist soil evaporation suggesting that water use by the understorey vegetation was substantial. However, in mature orchards with a high canopy cover (>55% fractional cover), orchard floor water losses were less than 30% of the measured ET. Understorey transpiration rates were much lower, contributing less than 10% of the whole orchard ET. Significant volumes of water can be saved, especially in young orchards, by keeping the orchard floor vegetation short, reducing the area occupied by understorey vegetation, and by reducing the wetted ground surface area. •Micro stem heat balance sap flow gauges can accurately measure grass sap flow.•Understorey vegetation had the greatest impact on water use in young orchards.•Understorey transpiration (Tc) can be predicted with the Priestley and Taylor model.•Tree canopy cover had a greater impact on Tc than the understorey leaf area index.